Why do infants imitate selectively?: neural correlates of infants’ action understanding in the head-touch paradigm - Langeloh, Miriam (2020)
Imitation is an important social learning mechanism for young infants exploring the world. Interestingly, infants do not imitate every action they observe – they rather do so selectively. Fourteen-month-olds predominantly imitated an unusual and inefficient action (turning on a lamp with one’s forehead) when the model’s hands were free compared to when the model’s hands were occupied (Gergely et al., 2002). Behavioral scientists have proposed contrasting explanatory accounts, differing with regard to the assumed level of infants’ cognitive abilities. Rational-imitation accounts suggest that infants selectively imitate unusual actions because they are surprised by the inefficiency of the action (Gergely & Csibra, 2003). In contrast, non-rational imitation accounts propose that selective imitation depends on more basic factors such as motor abilities (Paulus et al., 2011a,b). The integrative model by Zmyj and Buttelmann (2014) represents the first attempt to put together these opposing theories. Both accounts may operate on different processing levels. Bottom-up processes are related to non-rational imitation accounts, whereas top-down processing is based on the assumptions of the rational-imitation accounts. Despite the large body of behavioral research on selective imitation, the question of what are the neural mechanisms underlying these processes remains unanswered. In my dissertation, I aimed to uncover the underlying cognitive processes during the observation of head-touch actions by recording infants’ neurophysiological responses in three empirical studies. To test the assumptions of the top-down processes linked to the rational-imitation accounts, I examined neural markers associated with violation of expectation (VOE) in an adaptation of the head-touch paradigm. Overall, results suggest that 12- to 14-month-old infants, but not 9-month-old infants, display VOE when observing a person performing an inefficient head touch. This VOE response is context-dependent and is elicited when the model’s hands are free but not when the hands are restrained. In Study 1, VOE has been linked to a reduction in mu power in response to the unexpected head touch. In Study 2, this finding was extended such that when 12- to 14-month-old infants observed an unexpected head touch, their brains responded with increased attentional engagement (enhanced Nc amplitude) and a detection of a semantic violation (N400 component). Finally, in Study 3, in the absence of contextual information, 1-year-olds discriminated between hand- and head-touch outcomes on the Nc component only. Thus, infants require information of the action context to detect semantic violations within the head-touch paradigm. To conclude, the studies presented in my dissertation have paved the way to further our understanding of infants’ action perception and observational learning. Understanding the neural mechanisms of infants’ action perception in more depth, will help us to adequately foster the ideal observational learning conditions of novel actions. The results of this dissertation suggest that presenting infants with surprising action means puts them in an optimal receptive state for knowledge acquisition.